Encapsulated perovskite based photovoltaics devices with high stability. Issue 47 (2nd May 2016) - Wong, Man Kwong; Dong, Qi; Liu, Fangzhou; Djurišić, Aleksandra B.; Chan, Wai Kin; Li, Hangkong; Shih, Kaimin; Ng, Annie; Surya, Charles
ABSTRACT: Perovskite based photovoltaics have recently emerged as the forerunner in the next generation photovoltaic technology because of the rapid increase of power conversion efficiency (PCE). However, it is well recognized that the exposure to moisture, heat and light causes the degradation of perovskite [1] (especially for methylammonium lead iodide (CH3 NH3 PbI3 ) which is the most commonly used perovskite material). It makes stability a main issue for the commercialization of perovskite based photovoltaics. Hence, an advanced encapsulation method is one of the keys to improve the stability. Here we present a comparison study between different encapsulation methods. Perovskite based photovoltaics devices were encapsulated using UV epoxy resin, with or without the addition of desiccant and the deposition of SiO2 layer. By minimizing the ingress of moisture and oxygen, devices with storage in ambient air under one sun continuous illumination could retain 94 % of the initial performance (PCE around 13%) after two days.